Strategic Importance of Gwadar Port - Hasan Yaser Malik (Journal of Political Studies, 2012)
The pragmatic facets like geography and history have always imprinted the demographical mosaic and development of a civilisation. The civilisations have always developed along the waters. The waters have been used as trade route since long and the modern trade has further enhanced the need of trade through waters. Pakistan being a gateway to the strategically important 'Strait Of Hurmoz' in the Indian Ocean, blessed with hidden treasures and bordering two Islamic Republics, Afghanistan and Iran, has always been a centre piece for Regional Politics. The emergence of Gwadar Port as a vibrant regional economic hub has caused the regional and extra regional powers to develop strategic and infra structural development with Gwadar Port to reach the energy rich Central Asian Republics (CARs). Iran and Dubai Port World (UAE) have interests to keep Gwadar Port out of competition as it serves as a gateway to Strait of Hurmoz. Pakistan needs to be addressing all the concerns to make Gwadar as a regional energy corridor